PROFESIONALISME AKUNTAN PENDIDIK : PERSPEKTIF ATAU TRIGER KUALITAS LULUSAN AKUNTANSI DI ERA MASYARAKAT EKONOMI ASEAN - Mardjono, Enny Susilowati; Solikhan, Badingatus (JURNAL AKUNTANSI DAN AUDITING, 2014)
The research examines the effect competences, professional commitment of accountant educatorstoward The quality of graduates in accounting in facing Asean Economic Community. Thisresearch use sample consisted of 66 accountant educators private universities in Semarang.The data are taken with method of collecting data into questionnaires central. Selection ofsamples by using purposive sampling. The hypothesis testing model using Partial Least Squareanalysis (PLS). The result of the research indicated, Competences, Professional Commitment ofAccountant educators are factors that affect positively on The quality of graduates in Accounting.The positive result gives contribution that improving the quality of human resources, competenceand professional commitment educators accountant is a necessary condition for achieving thelevel of success in the future. These findings contribute that improving the quality of accountinggraduates through professional commitment strategies of educators accountants such asbeing independent, enhancement training and conferences, work teamwork and improving thecompetence that relevant with orientation of the accounting department and be able to evaluateobjectively learning will realize the Indonesian people who are ready to face the regional andglobal economy as AFTA (Asean Free Trade Area), APEC(Asia Pacific Economic Community),GATT (General Agreement on Tariffs and Trade)/ WTO (World Trade Organization), and tomeet the ASEAN Community 2015.